The Effect of The Values of Peace on The Ability of Youth to Face VUCA Era (VUCA Prime) - Siti Hardianti Darma Pertiwi; Idayanti Nursyamsi; Abdul Razak Munir (Program Pascasarjana STIE Amkop Makassar, 2023)
VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) is a phenomenon that can cause significant changes in an organization. However, the success of the organization in dealing with these changes is not only obtained by understanding VUCA but also by preparing itself for a strategy to deal with VUCA. The strategy is named VUCA Prime (Vision, Understanding, Clarity, Agility). This study connects the values of peace promoted by the KITA Bhinneka Tunggal Ika Foundation in the Peace Leadership Education program